Olfactory ensheathing cell membrane properties are shaped by connectivity - Rela, Lorena (2010)
Olfactory ensheathing cells (OECs) have been repeatedly implicated in mediating plasticity, particularly in situ in the olfactory nerve where they support the extension of olfactory sensory neuron (OSNs) axons from the olfactory epithelium to the olfactory bulb (OB). OECs are specialized glia whose processes surround OSN axon fascicles within the olfactory nerve and across the OB surface. Despite their purported importance in promoting axon extension, and following transplants, little is known about either morphology or biophysical properties of OECs in situ. In particular, cell-cell interactions that may influence OEC function are largely unexplored. Here, we studied OEC connectivity and morphology in slice preparations, preserving tissue structure and cell-cell interactions. Our analyses showed that OECs form a matrix of cellular projections surrounding axons, unique among glia, and express high levels of connexin-43. Lucifer Yellow injections revealed selective dye coupling among small subgroups of OECs. Two types of OECs were biophysically distinguished with whole cell voltage clamp recordings: 1) with low input resistance (Ri), linear current profiles, and frequently dye coupled; and 2) with high Ri, non-linear current profiles, and infrequent dye coupling. Pharmacological blockade of gap junctions changed OEC membrane properties such that linear OECs became non-linear. Double recordings indicated that the appearance of the non-linear current profile was associated with the loss of electrical coupling between OECs. We conclude that the diversity of OEC current profiles can be explained by differences in gap junction connectivity and discuss implications of this diversity for OEC influences on axon growth and excitability.